CONCEPTION OF DECREASING OF PREVENTABLE HEALTH LOSS IN CHILDREN - A.A. Baranov; V.Yu. Albitsky; R.N. Terletskaya; D.I. Zelinskaya ("Paediatrician" Publishers LLC, 2010)
Authors analyzed materials on modern estimation of health from a position of its loss on the stage of self-feeling forming from optimal to maximal level of disease (death). Indicators used for correct evaluation of health in foreign and Russian practice are presented. Specialists of Scientific Center of Children's Health, Russian Academy of Medical Sciences, developed conception of decreasing of preventable health loss as a consequence of chronic diseases, disability and death. This conception is newly developed concerning to children. Key words: preventable health loss, children, morbidity, disability, mortality.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(5):5-9)